Sal de ervas e a aceitabilidade em dietas hipossódicas no âmbito hospitalar - (:unkn) unknown (Universidade Federal do Pampa, 2018)
The hyposodic diet, at the hospital level has one of the lowest adherence rates. Rejection of this diet can lead to insufficient intake, which may result in inadequate energy and nutrients for the body. The objective of this research was to analyze the acceptability of herbal salt in hyposodium diets in a public hospital on the western border of Rio Grande do Sul. This is an observational study, descriptive, applied, cross-sectional and quantitative approach, involving 33 hospitalized patients. Sensory analysis was performed at the dinner meal, in two preparations with a hyposodic diet, where in one was added the salt of herbs and in another the salt of kitchen.Statistical analysis was performed using the statistical software GrapPad Instat, 3.00. The majority of patients were female, 22 women (66.6%) and 11 men (33.3%). There was no statistically significant difference between the samples regarding acceptance, (p = 0.3807) and to the seasoning (p = 0.3910) and both samples showed good acceptance. Considering the terms of the scale used, in both soups, the notes correspond to the term hedonic liked. It was concluded that the herb salt had good acceptability, considering the attributes flavor and seasoning. In addition, the results obtained in the intention test showed good acceptability. Thus, herbal salt proved to be an effective strategy to increase the palatability and decrease of dietary sodium.
Keywords: Especiarias; Dieta hipossódica; Estado nutricional; Spices; Hyposodic diet; Nutritional status; CNPQ::CIENCIAS DA SAUDE